IDENTIFIKASI KUMAN PADA PUS DARI LUKA INFEKSI KULIT - Evy Ratnasari Ekawati; Siti Nur Husnul Y.; Dheasy Herawati (Jurnal SainHealth, 2018)
Infectious lesions on the skin surface are easily colonized by various organisms. Pyogenic infections are still common, especially in developing countries and for therapeutic treatment is a big challenge. Ensure appropriate and efficient therapy, inflammation-focused identification and treatment is needed. The aim of this research was to identify germs isolated from pus sample in patients suffering from wound infentions on the skin surface. The type of this research is descriptive explorative. Pus sample were taken from two people who had an infection wound on the skin surface. In this research was found Pseudomonas aeruginosa with a similarity percentage of 90.7% and Staphylococcus aureus with a percentage similarity of 91.5 % in the pus sample.